PENGARUH MOTIVASI DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASIONAL (Studi Kasus Pada Guru SMA Negeri Se-Kota Tegal) - Wiryo Raharjo, 14.5202.0100; Sutomo, Y. (Jurnal Mahasiswa Pasca Sarjana, 2016)
The purpose of this study was to analyze the influence of motivation, professional competence, organizational culture on teacher performance and to analyze the influence of organizational culture in moderating the influence of motivation and professional competence on the performance of government school teachers in SMA as the city of Tegal. The object of this research is all teachers were civil servants in SMA as the city of Tegal. This research uses a quantitative research with a sample of 154 teachers. The analytical method used in this research is multiple linear regression. The method of collecting data in this study using a questionnaire with accidental techniqueÂ  and formula Slovin.Keywords: Performance, Organizational Culture, Motivation, Professional Competence